Generation of IgM+ B cell-deficient Atlantic salmon (Salmo salar) by CRISPR/Cas9-mediated IgM knockout - Mari Raudstein; Ma. Michelle D. Peñaranda; Erik Kjærner-Semb; Søren Grove; H. Craig Morton; Rolf Brudvik Edvardsen (Scientific Reports, 2025)
Abstract Infectious diseases pose significant challenges to Norwegian Atlantic salmon aquaculture. Vaccines are critical for disease prevention; however, a deeper understanding of the immune system is essential to improve vaccine efficacy. Immunoglobulin M (IgM) is the main antibody involved in the systemic immune response of teleosts, including Atlantic salmon. In this study, we used CRISPR/Cas9 technology to knock out the two IgM genes in Atlantic salmon. High-throughput sequencing revealed an average mutagenesis efficiency of 97% across both loci, with a predominance of frameshift mutations (78%). Gene expression analyses demonstrated significantly reduced membrane-bound IgM mRNA levels in head kidney and spleen tissues. Flow cytometry revealed a 78% reduction in IgM+ B cells in peripheral blood, and Western blot analyses showed decreased IgM protein levels in serum. Notably, an upregulation of IgT mRNA was observed, suggesting a potential compensatory mechanism. This work presents the first application of CRISPR/Cas9 to disrupt an immune-related gene in the F0 generation of Atlantic salmon, and lays the foundation for generating a model completely lacking IgM+ B cells which can be used to study the role of B cells and antibodies. This study has implications for advancing immune research in teleosts and for developing strategies to improve salmon health and welfare in aquaculture.